ACSM's sports medicine : a comprehensive review - O'Connor, Francis G. (Online access: Ovid Technologies LWW Doody's Core Collection 2019., 2013)
The field of sports medicine is evolving, accelerated by emerging technologies and changing health care policies. To stay up to speed and ace the Boards, you need a resource that moves at your pace. Sanctioned by the American College of Sports Medicine (ACSM), this handy review addresses all areas of the sports medicine subspecialty board examination--with coverage that spans the full spectrum of sports medicine, from medical to skeletal conditions related to the athlete. The editors and authors include orthopedic surgeons, family physicians, pediatricians, internal medicine specialists, physiatrists, certified athletic trainers, physical therapists, psychologists, nutritionists, exercise physiologists and more, ensuring that you'll benefit from the broad spectrum of expertise embraced by the specialty.